World cocoa survey - Krug, C. A.; Quartey-Papafio, E. (Rome : Food and Agriculture Organization of the United Nations, 1964)
It presents a global view of the cocoa situation at the time, what has been done in the past, and what may be expected in the future.
"Originally compiled...[for the] First FAO Technical Cocoa Meeting, held in Accra, Ghana, in February 1959...It has now...been brought up to date."
Includes bibliographical references: p. [239]-242.
oif 15/01/2019
Loans
Keywords: Cocoa; Cacao; Stimulant Crops